Comparison of Platelet Function Tests for Long-Term Cardiovascular Events after Percutaneous Coronary Interventions - Zhou, Mingyao; Hou, Pan; Liang, Ying; Tao, Wenqi; Guo, Zhifu; Zhang, Bili; Lu, Yang; Chu, Guojun; Li, Pan (Seminars in Thrombosis and Hemostasis, 2025)
Patients with high on-treatment platelet reactivity (HTPR) undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) face increased risks of major adverse cardiovascular events (MACEs). Although platelet function tests like thrombelastography (TEG), vasodilator-stimulated phosphoprotein (VASP), PL-11, and VerifyNow have been described, the correlation between them and their prognostic implications remains uncertain. This prospective study aims to evaluate the consistency and effectiveness of four platelet function detection methods in predicting long-term MACEs in patients with ACS. All 98 ACS patients undergoing PCI with clopidogrel were assessed for HTPR using four platelet function detection methods. The endpoint was the occurrence of MACEs, including cardiac death, nonfatal myocardial infarction (MI), and target vessel revascularization (TVR). Among 98 patients enrolled from April 1, 2014 to June 30, 2014, 27 (27.6%) patients with VerifyNow-detected HTPR (P2Y12 reaction units [PRUs] >240). The incidence of HTPR was 58.2% for TEG, 52% for VASP, and 13.3% for PL-11. VerifyNow and TEG showed the highest consistency in detecting HTPR (kappa = 0.201, p = 0.015). During a median follow-up of 6.1 years, 29 MACEs occurred, including 24 TVRs, 3 cardiovascular deaths, and 2 nonfatal MIs. VerifyNow-detected HTPR independently predicted long-term MACEs (hazard ratio: 5.73, 95% confidence interval: 2.04–16.09, p = 0.001), even after adjusting for traditional risk factors (TRFs). Receiver operating characteristic (ROC) analysis indicated that the model incorporating TRFs and VerifyNow-detected HTPR had superior predictive discrimination for MACEs (area under ROC curve = 0.889). VerifyNow-detected HTPR independently emerges as a robust predictor for long-term MACEs, demonstrating superior predictive discrimination compared with other platelet function tests.
Keywords: platelet function tests; major adverse cardiovascular event; VerifyNow; high on-treatment platelet reactivity